Motivations for a career in teaching: medical students’ projections towards their future role - Pilar González-Amarante; Manuel A. Romero-Padrón (BMC Medical Education)
Abstract Background Medical educators play a crucial role in the perpetuation of the medical profession. Recent concerns have arisen regarding the quality and quantity of current teachers. To comprehend this shortage, it is key to understand future physicians’ attitudes towards venturing in education, their motivations and possible detracting factors. This study aims to explore graduating students' attitudes towards a future teaching role and identify motivating and hindering factors. Methods Sixty-eight students in their final year of medical training answered a digital questionnaire. Responses were processed using descriptive statistics and qualitative coding for the open-ended questions. Results Teaching was the second most prevalent aspiring role (59%) after the clinical one. The most mentioned motivations were contribution to the future of medicine (50%), passion (31.8%) and sense of social duty (18%). Conversely, top hindering factors revealed non-economic disadvantages (85%), economic disadvantages (39.7%) and cost–benefit rationale (11.7%). Students’ recent experience across the undergraduate path provided insights about the influence of different agents, teachers’ exemplary attributes, and their own projection for their future role. Teaching is predominantly viewed as an honorable and aspirational role but constrained by inadequate economic compensation. Students feel confident on this path, with limited understanding of teacher professionalization. Conclusions Understanding students’ perspective in pursuing teaching careers offers insight that can address longstanding issues in the field. Strategic initiatives should focus on amplifying motivational factors, and addressing demotivational factors, like the lack of economic incentives, to strengthen the appeal of the teaching profession, and offer better resources to aspiring medical educators that may heighten their satisfaction and attract new aspiring professionals keeping high standards in their professionalization and performance.